Synthesis of some dihydropyrimidinone derivatives and study of their anti-inflammatory activity - Podilla, Naresh; Choudhury, Tirthankar (Journal of Applied Pharmaceutical Research, 2018)
This research revealed that the numbers of available heterocyclic compounds are mainly focused on nitrogen containing compounds, such as quinazolines, indoles, benzimidazole, quinoxalines, coumarins and pyrimidines etc. A mixture of substituted aldehydes (0.01 mol) like acetyl acetone (method 1) or ethyl acetoacetate (method 2), urea or thiourea (0.01 mol) and lemon juice (0.5 ml) were taken into a round bottom flask and reflux for 1 hour at 800C under continuous stirring. After completion of the reaction the final product was recrystalized for purification. Simultaneously toxicity and anti-inflammatory activity were performed. But in case of using ethyl acetoacetate in method 2, the percentage yield was more as compare to using of acetyl acetone in method 1. So the derivatives obtained from method 2 were selected for further toxicity and anti- inflammatory activities.